Precarity between a megacity and coastal erosion: A political economy of (un)managed retreat pathways in Thailand's peri-urban Khun Samut Chin - Danny Marks; Carl Middleton; Orapan Pratomlek (Ocean & Coastal Management, 2025)

‘People say, “It's just allergies”, so no one can be blamed:’ exploring social science drivers of PM 2.5 and climate obstruction through civil society perspectives in Thailand - Kelly E. Perry; Titta Buabut; Amana Parveen; Danny Marks (Climate and Development, 2025)

Perceptions of coastal vegetated ecosystems: A systematic review across geographical and sectoral dimensions - Jay Mar D. Quevedo; Michelle Ann Miller; Dixon T. Gevaña; Danny Marks; Daniel A. Friess; Prayoto Tonoto; David Taylor (Ambio, 2025)
Coastal vegetated ecosystems such as mangrove forests, seagrass meadows, and tidal marshes provide a wide array of ecosystem services. They also play a vital role in climate change mitigation through carbon sequestration. However, they are among the most threatened ecosystems globally. This study addresses a key knowledge gap by conducting a systematic review of academic literature on sectoral perceptions of these ecosystems. Through content analysis, we identified common research themes across regions and examined how members of the public, private, and civil society sectors perceive coastal vegetated ecosystems. The results reveal regional differences: Asian countries tend to emphasize utilization and economic benefits, while North America and Europe focus more on conservation and management. Several studies explored perceptions of climate change mitigation. Our findings highlight gaps in perception between the private and government agencies. Understanding these diverse sectoral perspectives can inform policy interventions to enhance conservation efforts and strengthen governance strategies.

Cerebral hypoperfusion, brain structural integrity, and cognitive impairment in older APOE4 carriers - Ioannis Pappas; Trevor Lohman; Shubir Dutt; Arunima Kapoor; Allison C. Engstrom; John Paul M. Alitin; Samuel Barnes; Ararat Chakhoyan; Lucas Saca; Raghav Gaggar; Elnaz Nourollahimoghadam; Danny J. J. Wang; et al. (GeroScience, 2025)
Cerebral blood flow (CBF) deficits, cognitive decline, and brain structural changes have been reported in older adults with and without apolipoprotein E-e4 ( APOE4 )-related risk for dementia. However, it remains unclear whether brain structural changes mediate the effects of hypoperfusion on cognitive impairment in APOE4 carriers and non-carriers. We studied 166 (60–89 years) APOE4 carriers (ε3/ε4 or ε4/ε4) and APOE3 homozygotes (e3/e3) with and without cognitive impairment by clinical dementia rating (CDR) and neuropsychological testing. Pseudocontinuous arterial spin-labeling-MRI assessed regional CBF, and T1-anatomical and diffusion-MRI assessed structural integrity. Mediation analyses examined relationships among grey matter CBF, grey matter volume, and white matter integrity in regions underlying impairment in distinct cognitive ability domains. APOE4 carriers with global/memory impairment (CDR 0.5) exhibited decreased CBF in the posterior cingulate, decreased grey matter volume in the hippocampus, parahippocampal gyrus, and posterior cingulate, and decreased white matter integrity in the cingulum relative to APOE4 carriers with no impairment (CDR 0). Mediation analysis in APOE4 carriers indicated decreased posterior cingulate CBF effects on global/memory impairment were mediated by decreased cingulum integrity. In the combined APOE4 and APOE3 carriers sample, there were direct effects of frontal and inferior parietal CBF and superior longitudinal fasciculus integrity on attention/executive impairment. There were also direct effects of left inferior frontal CBF on language impairment. Findings suggest links between hypoperfusion and brain structural integrity underlying global/memory impairment in APOE4 carriers. Independent CBF relationships with structural integrity are also identified across genotypes and impairment domains.

Abundance survey of crustacean “y-larvae” (Thecostraca: Facetotecta) over a fringing reef in Okinawa, Japan, with special reference to the two dominant planktotrophic and lecithotrophic naupliar types - Jørgen Olesen; Mark J. Grygier; Ferran Palero; Niklas Dreyer; Danny Eibye-Jacobsen; Yoshihisa Fujita (Marine Biodiversity, 2025)
Facetotecta, or “y-larvae”, are mysterious planktonic crustaceans that are known only from their larval instars, but which are often assumed to be endoparasitic as adults. Dozens of mostly undescribed forms occur in the shallow-water plankton over a fringing reef at Sesoko Island, Okinawa, Japan. Recently, it has become possible to discriminate the different forms of their nauplius-stage larvae (“y-nauplii”) in a replicable way. A large year-to-year overlap in morphospecies recovered during fieldwork at Sesoko Island in 2018, 2019, and 2023 suggests that a full inventory is close at hand. To date, 49 morphospecies of y-nauplii (8 planktotrophic, 41 lecithotrophic) have been recognized in the area, among which three have been formally described. A detailed analysis of the temporal fluctuations in abundance during October 2023 showed that most morphospecies were rare, but two were particularly common: Type A*, a planktotroph with a long (> 3 weeks) period of naupliar development allowing for long-distance dispersal, and Type AG*, a lecithotroph with a short (3 days) period of development that implies rapid local recolonization. During the survey, both types showed distinct, largely non-overlapping peaks in abundance, related perhaps to their different dispersal/feeding strategies. An examination of the morphology of the swimming/feeding appendages in y-nauplii of Types A* and AG*, together with a mapping of feeding versus non-feeding nauplii on a recent comprehensive phylogeny of Facetotecta, suggests that broader taxonomic coverage of naupliar feeding structures in this group may provide useful information regarding the evolutionary direction of planktotrophy versus lecithotrophy in marine larvae.

The role of vasculature and angiogenesis in respiratory diseases - Maximilian Ackermann; Christopher Werlein; Edith Plucinski; Sophie Leypold; Mark P. Kühnel; Stijn E. Verleden; Hassan A. Khalil; Florian Länger; Tobias Welte; Steven J. Mentzer; Danny D. Jonigk (Angiogenesis, 2024)
In European countries, nearly 10% of all hospital admissions are related to respiratory diseases, mainly chronic life-threatening diseases such as COPD, pulmonary hypertension, IPF or lung cancer. The contribution of blood vessels and angiogenesis to lung regeneration, remodeling and disease progression has been increasingly appreciated. The vascular supply of the lung shows the peculiarity of dual perfusion of the pulmonary circulation (vasa publica), which maintains a functional blood-gas barrier, and the bronchial circulation (vasa privata), which reveals a profiled capacity for angiogenesis (namely intussusceptive and sprouting angiogenesis) and alveolar-vascular remodeling by the recruitment of endothelial precursor cells. The aim of this review is to outline the importance of vascular remodeling and angiogenesis in a variety of non-neoplastic and neoplastic acute and chronic respiratory diseases such as lung infection, COPD, lung fibrosis, pulmonary hypertension and lung cancer.

Inflammation and vascular remodeling in COVID-19 hearts - Christopher Werlein; Maximilian Ackermann; Helge Stark; Harshit R. Shah; Alexandar Tzankov; Jasmin Dinonne Haslbauer; Saskia von Stillfried; Roman David Bülow; Ali El-Armouche; Stephan Kuenzel; Jan Lukas Robertus; Marius Reichardt; et al. (Angiogenesis, 2023)
A wide range of cardiac symptoms have been observed in COVID-19 patients, often significantly influencing the clinical outcome. While the pathophysiology of pulmonary COVID-19 manifestation has been substantially unraveled, the underlying pathomechanisms of cardiac involvement in COVID-19 are largely unknown. In this multicentre study, we performed a comprehensive analysis of heart samples from 24 autopsies with confirmed SARS-CoV-2 infection and compared them to samples of age-matched Influenza H1N1 A ( n = 16), lymphocytic non-influenza myocarditis cases ( n = 8), and non-inflamed heart tissue ( n = 9). We employed conventional histopathology, multiplexed immunohistochemistry (MPX), microvascular corrosion casting, scanning electron microscopy, X-ray phase-contrast tomography using synchrotron radiation, and direct multiplexed measurements of gene expression, to assess morphological and molecular changes holistically. Based on histopathology, none of the COVID-19 samples fulfilled the established diagnostic criteria of viral myocarditis. However, quantification via MPX showed a significant increase in perivascular CD11b/TIE2 + —macrophages in COVID-19 over time, which was not observed in influenza or non-SARS-CoV-2 viral myocarditis patients. Ultrastructurally, a significant increase in intussusceptive angiogenesis as well as multifocal thrombi, inapparent in conventional morphological analysis, could be demonstrated. In line with this, on a molecular level, COVID-19 hearts displayed a distinct expression pattern of genes primarily coding for factors involved in angiogenesis and epithelial-mesenchymal transition (EMT), changes not seen in any of the other patient groups. We conclude that cardiac involvement in COVID-19 is an angiocentric macrophage-driven inflammatory process, distinct from classical anti-viral inflammatory responses, and substantially underappreciated by conventional histopathologic analysis. For the first time, we have observed intussusceptive angiogenesis in cardiac tissue, which we previously identified as the linchpin of vascular remodeling in COVID-19 pneumonia, as a pathognomic sign in affected hearts. Moreover, we identified CD11b + /TIE2 + macrophages as the drivers of intussusceptive angiogenesis and set forward a putative model for the molecular regulation of vascular alterations.

Closing the loop or widening the gap? The unequal politics of Thailand's circular economy in addressing marine plastic pollution - Danny Marks; Michelle Ann Miller; Sujitra Vassanadumrongdee (Journal of Cleaner Production, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

Disentangling the concepts of global climate change, adaptation, and human mobility: a political-ecological exploration in Vietnam’s Mekong Delta - Mucahid Mustafa Bayrak; Danny Marks; Leon T. Hauser (Climate and Development, 2022)

Evaluation of sediment capping effectiveness in Hyeongsan River for in-situ management of total mercury and methylmercury contamination - Dhiraj Kumar Chaudhary; Mark Xavier Bailon; Hwansuk Kim; Danny Reible; Yongseok Hong (Journal of Soils and Sediments, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Towards a cultural lens for adaptation pathways to climate change - Danny Marks; Mucahid Mustafa Bayrak; Selim Jahangir; David Henig; Ajay Bailey (Regional Environmental Change, 2022)
Adaptation pathways have been conventionally viewed as an approach for planning and identifying different adaptation options and the ways in which they can be realized. However, there has been scant consideration of the wide diversity of cultural and social processes which shape how adaptation pathways emerge. We argue that a cultural lens sheds light on differential vulnerability and the processes that enable or hinder adaptation. A cultural lens focuses intrinsically on intersectional categories which can impact the adaptive agency or resilience of individuals, households, and communities. In particular, we need to examine how cultural beliefs, norms, and practices change over time, and are reflected in adaptation pathways since livelihoods do not remain the same over the life course. Additionally, taking a broader perspective by incorporating concepts from cognitive anthropology helps us understand motivations and choices which influence adaptation pathways.

Land‐use type temporarily affects active pond community structure but not gene expression patterns - Mina Bizic; Danny Ionescu; Rajat Karnatak; Camille L. Musseau; Gabriela Onandia; Stella A. Berger; Jens C. Nejstgaard; Gunnar Lischeid; Mark O. Gessner; Sabine Wollrab; Hans‐Peter Grossart (Molecular Ecology, 2022)
Changes in land use and agricultural intensification threaten biodiversity and ecosystem functioning of small water bodies. We studied 67 kettle holes (KH) in an agricultural landscape in northeastern Germany using landscape‐scale metatranscriptomics to understand the responses of active bacterial, archaeal and eukaryotic communities to land‐use type. These KH are proxies of the millions of small standing water bodies of glacial origin spread across the northern hemisphere. Like other landscapes in Europe, the study area has been used for intensive agriculture since the 1950s. In contrast to a parallel environmental DNA study that suggests the homogenization of biodiversity across KH, conceivably resulting from long‐lasting intensive agriculture, land‐use type affected the structure of the active KH communities during spring crop fertilization, but not a month later. This effect was more pronounced for eukaryotes than for bacteria. In contrast, gene expression patterns did not differ between months or across land‐use types, suggesting a high degree of functional redundancy across the KH communities. Variability in gene expression was best explained by active bacterial and eukaryotic community structures, suggesting that these changes in functioning are primarily driven by interactions between organisms. Our results indicate that influences of the surrounding landscape result in temporary changes in the activity of different community members. Thus, even in KH where biodiversity has been homogenized, communities continue to respond to land management. This potential needs to be considered when developing sustainable management options for restoration purposes and for successful mitigation of further biodiversity loss in agricultural landscapes.

Animal Borne Ocean Sensors – AniBOS – An Essential Component of the Global Ocean Observing System - Clive R. McMahon; Fabien Roquet; Sophie Baudel; Mathieu Belbeoch; Sophie Bestley; Clint Blight; Lars Boehme; Fiona Carse; Daniel P. Costa; Michael A. Fedak; Christophe Guinet; Robert Harcourt; et al. (Frontiers in Marine Science, 2021)
Marine animals equipped with biological and physical electronic sensors have produced long-term data streams on key marine environmental variables, hydrography, animal behavior and ecology. These data are an essential component of the Global Ocean Observing System (GOOS). The Animal Borne Ocean Sensors (AniBOS) network aims to coordinate the long-term collection and delivery of marine data streams, providing a complementary capability to other GOOS networks that monitor Essential Ocean Variables (EOVs), essential climate variables (ECVs) and essential biodiversity variables (EBVs). AniBOS augments observations of temperature and salinity within the upper ocean, in areas that are under-sampled, providing information that is urgently needed for an improved understanding of climate and ocean variability and for forecasting. Additionally, measurements of chlorophyll fluorescence and dissolved oxygen concentrations are emerging. The observations AniBOS provides are used widely across the research, modeling and operational oceanographic communities. High latitude, shallow coastal shelves and tropical seas have historically been sampled poorly with traditional observing platforms for many reasons including sea ice presence, limited satellite coverage and logistical costs. Animal-borne sensors are helping to fill that gap by collecting and transmitting in near real time an average of 500 temperature-salinity-depth profiles per animal annually and, when instruments are recovered (∼30% of instruments deployed annually, n = 103 ± 34), up to 1,000 profiles per month in these regions. Increased observations from under-sampled regions greatly improve the accuracy and confidence in estimates of ocean state and improve studies of climate variability by delivering data that refine climate prediction estimates at regional and global scales. The GOOS Observations Coordination Group (OCG) reviews, advises on and coordinates activities across the global ocean observing networks to strengthen the effective implementation of the system. AniBOS was formally recognized in 2020 as a GOOS network. This improves our ability to observe the ocean’s structure and animals that live in them more comprehensively, concomitantly improving our understanding of global ocean and climate processes for societal benefit consistent with the UN Sustainability Goals 13 and 14: Climate and Life below Water. Working within the GOOS OCG framework ensures that AniBOS is an essential component of an integrated Global Ocean Observing System.

Increased connectivity and depth improve the effectiveness of marine reserves - Jordan S. Goetze; Shaun Wilson; Ben Radford; Rebecca Fisher; Tim J. Langlois; Jacquomo Monk; Nathan A. Knott; Hamish Malcolm; Leanne M. Currey‐Randall; Daniel Ierodiaconou; David Harasti; Neville Barrett; et al. (Global Change Biology, 2021)
Marine reserves are a key tool for the conservation of marine biodiversity, yet only ~2.5% of the world's oceans are protected. The integration of marine reserves into connected networks representing all habitats has been encouraged by international agreements, yet the benefits of this design has not been tested empirically. Australia has one of the largest systems of marine reserves, providing a rare opportunity to assess how connectivity influences conservation success. An Australia‐wide dataset was collected using baited remote underwater video systems deployed across a depth range from 0 to 100 m to assess the effectiveness of marine reserves for protecting teleosts subject to commercial and recreational fishing. A meta‐analytical comparison of 73 fished species within 91 marine reserves found that, on average, marine reserves had 28% greater abundance and 53% greater biomass of fished species compared to adjacent areas open to fishing. However, benefits of protection were not observed across all reserves (heterogeneity), so full subsets generalized additive modelling was used to consider factors that influence marine reserve effectiveness, including distance‐based and ecological metrics of connectivity among reserves. Our results suggest that increased connectivity and depth improve the aforementioned marine reserve benefits and that these factors should be considered to optimize such benefits over time. We provide important guidance on factors to consider when implementing marine reserves for the purpose of increasing the abundance and size of fished species, given the expected increase in coverage globally. We show that marine reserves that are highly protected (no‐take) and designed to optimize connectivity, size and depth range can provide an effective conservation strategy for fished species in temperate and tropical waters within an overarching marine biodiversity conservation framework.

A Continental-Scale Validation of Ecosystem Service Models - Simon Willcock; Danny A. P. Hooftman; Stefano Balbi; Ryan Blanchard; Terence P. Dawson; Patrick J. O’Farrell; Thomas Hickler; Malcolm D. Hudson; Mats Lindeskog; Javier Martinez-Lopez; Mark Mulligan; Belinda Reyers; et al. (Ecosystems, 2019)

Long-term recovery narratives following major disasters in Southeast Asia - Frank Thomalla; Louis Lebel; Michael Boyland; Danny Marks; Ham Kimkong; Sinh Bach Tan; Agus Nugroho (Regional Environmental Change, 2018)

Responses to the 2011 floods in Central Thailand: Perpetuating the vulnerability of small and medium enterprises? - Danny Marks; Frank Thomalla (Natural Hazards, 2017)

Airway remodelling in the transplanted lung - Mark Kuehnel; Lavinia Maegel; Jens Vogel-Claussen; Jan Lukas Robertus; Danny Jonigk (Cell and Tissue Research, 2017)

Starch productivity in cyclically operated photobioreactors with marine microalgae—effect of ammonium addition regime and volume exchange ratio - Peter R. Mooij; Danny R. de Graaff; Mark C. M. van Loosdrecht; Robbert Kleerebezem (Journal of Applied Phycology, 2015)

Mitochondrial DNA damage by bleomycin induces AML cell death - ManTek Yeung; Rose Hurren; Carine Nemr; Xiaoming Wang; Samantha Hershenfeld; Marcela Gronda; Sanduni Liyanage; Yan Wu; Jeevan Augustine; Eric A. Lee; Paul A. Spagnuolo; Noel Southall; et al. (Apoptosis, 2015)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Stability of Protein Pharmaceuticals: An Update - Mark Cornell Manning; Danny K. Chou; Brian M. Murphy; Robert W. Payne; Derrick S. Katayama (Pharmaceutical Research, 2010)

The effect of arm abduction angle and contraction intensity on perceived exertion - Mark K. Timmons; Staci M. Stevens; Danny M. Pincivero (European Journal of Applied Physiology, 2009)

Components and Controls of Water Flux in an Old-growth Douglas-fir?Western Hemlock Ecosystem - MichaelH. Unsworth; Nathan Phillips; T. Link; BarbaraJ. Bond; Matthias Falk; MarkE. Harmon; ThomasM. Hinckley; Danny Marks; KyawTha Paw U (Ecosystems, 2004)

Effects of habitat fragmentation on the fitness of two common wetland species, Carex davalliana and Succisa pratensis - Danny A. Hooftman; Mark van Kleunen; Matthias Diemer (Oecologia, 2003)

Persistent Inhibition of CYP3A4 by Ketoconazole in Modified Caco-2 Cells - Megan A. Gibbs; Mark T. Baillie; Danny D. Shen; Kent L. Kunze; Kenneth E. Thummel (Pharmaceutical Research, 2000)

Eucalyptus has a functional equivalent of the Arabidopsis floral meristem identity gene LEAFY - Simon G. Southerton; Steven H. Strauss; Mark R. Olive; Rebecca L. Harcourt; Veronique Decroocq; Xiaomei Zhu; Danny J. Llewellyn; W. James Peacock; Elizabeth S. Dennis (Plant Molecular Biology, 1998)